ANALISA PERBANDINGAN STORE IMAGE KONSUMEN ANTARA HYPERMARKET TOKO INDEPENDEN DAN HYPERMARKET DI PUSAT PERBELANJAAN - Edwin Japarianto (Institute of Research and Community Outreach - Petra Christian University, 2015)
This research was conducted to analyze the comparative of store image between Hypermarket at shopping centre and Hypermarket as independent store using perceptual mapping method. The research was conducted with distributing questioner to 300 respondents who has been shopping at least twice at one or both of those retail hypermarkets. Analysis tool which is used in this study is the analysis of Multidimensional Scaling (MDS).The results showed that each hypermarket has unique characteristics that require different management strategies.